The Role of Biomarkers in the Early Diagnosis of Gastric Cancer: A Study on CCR5, CCL5, PDGF, and EphA7 - Süleyman Bademler; Berkay Kılıç; Muhammed Üçüncü; Alisan Zirtiloglu; Burak İlhan (Current Issues in Molecular Biology)
Despite the use of screening programs, gastric cancer (GC) diagnosis may only be possible at an advanced stage. In this study, we examined the serum levels of C-C chemokine receptor type 5 (CCR5), C-C motif chemokine ligand 5 (CCL5), platelet-derived growth factor (PDGF), and EphrinA7 (EphA7) in patients with gastric carcinoma and healthy controls to investigate the significance and usability of these potential biomarkers in the early diagnosis of GC. The study enrolled 69 GC patients and 40 healthy individuals. CCR5, CCL5, PDGF-BB, and EphA7 levels, which have been identified in the carcinogenesis of many cancers, were measured in the blood samples using the ELISA method. CCR5, CCL5, PDGF-BB, and EphA7 were all correlated with GC diagnosis (CCR5, p < 0.001, r = −0.449; CCL5, p = 0.014, r = −0.234; PDGF-BB, p < 0.001, r = −0.700; EPHA7, p < 0.001, r = −0.617). The serum CCR5, EphA7, and especially the PDGF-BB levels of the patients diagnosed with GC were discovered to be significantly higher compared to the healthy controls. PDGF-BB had the highest positive and negative predictive values when evaluated in ROC analysis to determine its diagnostic significance (cut-off value: 59.8 ng/L; AUC: 0.92 (0.87–0.97)). As far as we know, this is the first study to investigate the potential connection between GC and these four biomarkers. The fact that serum CCR5, CCL5, EphA7, and especially PDGF-BB levels in the patient group were significantly higher compared to healthy controls indicates that they can be used with high accuracy in the early diagnosis of GC. In addition, the levels of CCR5, PDGF-BB, and EphA7 can be used as important indicators to predict the biological behavior and prognosis of GC.